DAMPAK KEBIJAKAN TATANIAGA PUPUK TERHADAP PERAN KOPERASI UNIT DESA SEBAGAI DISTRIBUTOR PUPUK - ILHAM, NYAK (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Fertilizers marketing policy that have been decided by the government on December 1998 is aimed at creating opportunity for suppliers or importers to supply and distribute fertilizers for the farmers. The problem is that the Cooperation of Village Unit Cooperation (KUDs) as distributors at Lini-IV will compete with supplier or importer who has more capital and good management. The aim of this paper is to asses the impact of zero subsidies and free market policy of fertilizers distribution system and the performance of Cooperation of Village Unit Cooperation (KUDs). This research has been carried out by the Center for Agro-socio Economic Research (CASER), by taking Karawang and Subang (West Java) as cases. The primary data were collected from PT. Pusri, SP. Bimas of Department of Agriculture, Fertilizer Retailers and Cooperation of Village Unit Cooperation (KUDs). The secondary data were collected from PT. Pusri. The finding of this research shows that, after the implementation of the policy, fertilizer distribution system becomes shorter (simpler) and fertilizers are distributed through many channels, so that farmers can buy fertilizers easily and at relatively low prices. Because of capital constraint, KUDs can not compete with non Cooperation of Village Unit Cooperation (non-KUDs) distributors. Consequently, the sale of KUDs fertilizers had decreased, and this condition will disturb the survival of Cooperation of Village Unit Cooperation (KUDs) as a distributors. In the long run, government must be aware of the possibility that non Cooperation of Village Unit Cooperation (non-KUDs) distributors form a cartel and have strong power in fertilizer marketing. To stabilize the contribution of Cooperation of Village Unit Cooperation (KUDs) as public institution in fertilizer distribution activity, government needs to empower Cooperation of Village Unit Cooperation (KUDs) through increasing working capital and coordinating fertilizer distribution mechanism through Center of Village Unit Cooperation (PUSKUDs).
Keywords: Fertilizer Marketing Policy, Cooperation of Village Unit, Distributor of Fertilizer